KEMAMPUAN MEMBACA TEKS DESKRIPSI SISWA KELAS VIII SMP NEGERI 2 KUTA (KUNDUR UTARA) - Lesdinarty, Trisintya; Mustafa, M. Nur; Razak, Abdul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The descriptive reading comprehension ability of eighth grade students in SMP Negeri 2 KUTA (North Kundur) aims to know what is the level of the descriptive reading comprehension ability of eighth grade students in SMP Negeri 2 KUTA (North Kundur) and to know is there the difference of the descriptive reading comprehension ability of eighth grade students in SMP Negeri 2 KUTA (North Kundur) between classes reading is one aspect of indonesian language teaching in various school. One the activites of reading is reading understanding, where to produce a perfect reading have to do the reading skill of understanding this description text is a text which describe a real object. The method which used for this research is quantitative method. This test is carried out using parametric test, where the test uses one sample t test and one-way ANOVA test. Based on the result of the test, the conclution that the descriptive reading comprehension ability of eighth grade students in SMP Negeri 2 KUTA (North Kundur) was very low and there were the differences of the descriptive reading comprehension ability of eighth grade students in SMP Negeri 2 KUTA (North Kundur) between classes.Key Words: Descriptive text, reading comprehension.